Teaching Materials through Local Wisdom in Implementing Independent Curriculum to Improve Teaching Skills for Indonesian Pre-Service Teacher - Susi Darihastining; Chalimah Chalimah; Wiwik Mardiana (Universitas Veteran Bangun Nusantara, 2022)
The role of lecturers in designing the teaching materials is very decisive successful learning and learning process through a teaching material. Teaching materials can also be interpreted as any form of materials arranged systematically that allows students to learn independently and are designed according to the applicable curriculum. The teaching material is unique and specific to achieve the learning objectives. Culture is a method for pre-service teachers to transform the results of observation into form and creative teaching material. The problem is appointed how the design of the teaching material through local wisdom as a form of independent curriculum application used by pre service teachers and lecturers in designing learning design that supports the independent freedom curriculum in the digital era. Research is in classroom action research. The research data is a design of teaching material in the form of learning design. The data sources were pre-service teachers who took the Micro Teaching course with 20 pre-service teachers as class of 2019 in academic year 2021/2022. Culture is also considered as a teaching material in the teaching and learning process. The application of E-PUB as the device of teaching material. The data collection technique is observation, documentation, and interview. The research instrument uses two aspects, namely: skill in arranging lesson plan and learning practice. The indicators of success are: (a) material understanding, (b) curriculum understanding, (c) learning practice, and (d) personality. The result of cycle I, 75% in sufficient category so it needs to continue to the next cycle. The result of cycle II is 91,66% is in very good category, 6,67 % is in good category and only one student is in fairly good category that is successful in cycle II in applying E-PUB.